Natural bioactive compounds modified with mesenchymal stem cells: new hope for regenerative medicine - Wu, Jingjing; Ge, Ying; Huang, Wendi; Zhang, Li; Huang, Juan; Huang, Nanqu; Luo, Yong (Frontiers in Bioengineering and Biotechnology, 2025)
Mesenchymal stem cells (MSCs) have the potential to differentiate into various cell types, providing important sources of cells for the development of regenerative medicine. Although MSCs have various advantages, there are also various problems, such as the low survival rate of transplanted cells and poor migration and homing; therefore, determining how to reform MSCs to improve their utilization is particularly important. Although many natural bioactive compounds have shown great potential for improving MSCs, many mechanisms and pathways are involved; however, in the final analysis, natural bioactive compounds promoted MSC proliferation, migration and homing and promoted differentiation and antiaging. This article reviews the regulatory effects of natural bioactive compounds on MSCs to provide new ideas for the therapeutic effects of modified MSCs on diseases.